Cloning, sequencing and analysis of the structural gene and regulatory region of the Pseudomonas aeruginosa chromosomal ampC beta-lactamase. - Lodge, J M (1990)
The chromosomal gene from Pseudomonas aeruginosa encoding beta-lactamase has been cloned, and the sequence determined and compared with corresponding sequences of beta-lactamases from members of the enterobacteriaceae. Upstream of the beta-lactamase gene is an open reading frame which we postulate encodes a regulatory protein, AmpR. We identified a helix-turn-helix region in AmpR and a putative AmpR-binding site.